Potent Neutralization Ability of a Human Monoclonal Antibody Against Serotype 1 Dengue Virus - Lu, Jiansheng; Wang, Rong; Xia, Binghui; Yu, Yunzhou; Zhou, Xiaowei; Yang, Zhixin; Huang, Peitang (Frontiers in Microbiology, 2018)
The incidence of dengue virus (DENV) infections has been escalating in tropical and subtropical countries, but there are still no effective therapeutic options. In the present study, a DENV-1-specific human monoclonal antibody (HMAb), 1G5, isolated from single plasma cells obtained from the peripheral blood mononuclear cells of dengue patients was found to have potent neutralization activity against serotype 1 DENV (DENV-1). Its neutralization activity against DENV-2 was not as strong, and it was almost absent for DENV-3 and DENV-4. The results showed that HMAb 1G5 only binds to the envelop protein of intact DENV-1 or the envelop protein under unheated and non-reducing conditions, and that it does not bind to recombinant envelope protein. This could mean that the antibody recognizes a conformational epitope of the envelope protein. Further, the findings showed that HMAb 1G5 potently neutralizes DENV-1 in both the pre- and post-attachment phases of the virus at low concentrations. In vivo studies showed that HMAb 1G5 provides protection from DENV-1 infection in a murine model. In addition, antibody-dependent enhancement that occurs at lower doses of the antibody was completely abrogated by the introduction of Leu-to-Ala mutations (1G5-LALA) or deletion of nine amino acids (1G5-9del) in the Fc region. Therefore, HMAb 1G5 shows promise as a safe and effective agent for prophylactic and therapeutic treatment of DENV-1 infection.